2007
DOI: 10.1111/j.1537-2995.2007.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated collection of double red blood cell units with a variable‐volume separation chamber

Abstract: BACKGROUND: Automated collection of blood components offers multiple advantages and has prompted development of portable devices. This study sought to document the biochemical and hematologic properties and in vivo recovery of red cells (RBCs) collected via a new device that employed a variable-volume centrifugal separation chamber. STUDY DESIGN AND METHODS:Normal subjects (n = 153) donated 2 units of RBCs via an automated blood collection system (Cymbal, Haemonetics). Procedures were conducted with wall outle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
2
9
2
1
Order By: Relevance
“…A number of different automated devices are capable of collecting red cells, either alone or concurrently with other blood components, and a number of studies on this have been previously reported (Greenwalt et al , 2002; Snyder et al , 2003; Picker et al , 2007; AuBuchon et al , 2008). A comprehensive study of the quality of leucoreduced RCC collected using the Amicus and Alyx separators (Fenwal, Deerfield, IL, USA), the MCS+ (Haemonetics, Braintree, MA, USA) and the Trima (CaridianBCT, Lakewood, CO, USA) found that the RCC met all regulatory requirements during their storage period (Picker et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of different automated devices are capable of collecting red cells, either alone or concurrently with other blood components, and a number of studies on this have been previously reported (Greenwalt et al , 2002; Snyder et al , 2003; Picker et al , 2007; AuBuchon et al , 2008). A comprehensive study of the quality of leucoreduced RCC collected using the Amicus and Alyx separators (Fenwal, Deerfield, IL, USA), the MCS+ (Haemonetics, Braintree, MA, USA) and the Trima (CaridianBCT, Lakewood, CO, USA) found that the RCC met all regulatory requirements during their storage period (Picker et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The Cymbal (Haemonetics) is a portable automated red cell collection device that allows the separation of variable volumes of blood in its centrifuge chamber. Leucoreduced RCC collected by the Cymbal using CP2D anticoagulant and stored in AS‐3 optimal additive solution have been shown to be of acceptable quality , as judged by in vitro analysis and in vivo recovery (AuBuchon et al , 2008) , but there are no published reports on the quality of RCC collected using the Cymbal with citrate, phosphate and dextrose (CPD‐50) anticoagulant and stored in saline, adenine, glucose and mannitol (SAGM) optimal additive solution, which is currently used for the collection of WB‐derived RCC in the United Kingdom. It was therefore necessary to conduct an investigation of the quality of Cymbal RCC stored in SAGM.…”
mentioning
confidence: 99%
“…7 Mean percentages of hemolysis for stored ARBC, as reported in the literature, ranged from .05% to .8%. 1,7,[10][11][12] This variation may likely be related to the different apheresis machines and to the different additive solutions that various study groups used.…”
Section: Sciencementioning
confidence: 95%
“…Total Hb (Sysmex XE2100, Sysmex, Mundelein, IL) and spun hematocrit were determined for each tube. Protein was extracted from each tube with 8% perchloric acid method as previously described 16 . The extracted supernatants were frozen at less than −75°C until assayed.…”
Section: Methodsmentioning
confidence: 99%
“…Protein was extracted from each tube with 8% perchloric acid method as previously described. 16 The extracted supernatants were frozen at less than -75°C until assayed. The neutralized perchloric acid extracts were analyzed for ATP using the NADP+ reduction method of Beutler 17 automated for the Cobas Fara.…”
Section: Methodsmentioning
confidence: 99%